Effect of S-nitrosoglutathione on arterial stiffness in women with severe preeclampsia and healthy controls. (18th April 2012) - Everett, TR; Mahendru, AA; McEniery, CM; Wilkinson, IB; Lees, CC
Abstract : Introduction: Pre-eclampsia and increased arterial stiffness are associated with cardiovascular disease later in life. Arterial stiffness is raised in preeclampsia. Augmentation index (AIx) is a non-invasive method of assessing arterial stiffness. Despite evidence of endothelial dysfunction in pre-eclampsia, there is no pharmacotherapeutic substance targeted at this underlying pathophysiology. S-nitrosoglutathione (GSNO) is an endogenously occurring nitric oxide donor that may ameliorate endothelial dysfunction. We performed intravenous GSNO infusions in healthy non-pregnant volunteers and women with severe preeclampsia. Methods: Controls: Four healthy volunteers underwent GSNO infusion at 10 and 30mcg/min. Doses were increased at 30min intervals maintaining BP >110/60mmHg. Pre-eclampsia: Four women with early-onset preeclampsia underwent GSNO infusion at 10 and 30mcg/min. Doses were increased at 30min intervals maintaining BP >140/80mmHg. For each infusion, AIx was assessed pre- and post-infusion and at each dose point. AIx and mean arterial pressure (MAP) were compared to initial readings at each dose using a paired t-test. Results: Controls: Significant reduction in AIx was seen at 10mcg/min (p=0.025) and 30mcg/min (p=0.005). No reduction in MAP was seen. Pre-eclampsia: No changes in AIx, and a small reduction in MAP (4mmHg, p=0.02), were seen at 10mcg/min (p=0.02). At 30mcg/min GSNO, AIx significantly reduced (p=0.02) and MAP remained unchanged Conclusion: GSNO infusion in early-onset preeclampsia and healthy volunteers can significantly decrease arterial stiffness with only minimal effect on MAP. Our results suggest GSNO may be a useful adjunct to current antihypertensive treatment for preeclampsia and a Phase 1 trial is planned.